مدى تطبيق المعيار المحاسبي الإسلامي رقم (2) المرابحة والمرابحة بالشراء في البنوك الإسلامية الكويتية ومعوقات تطبيقها = The extent of application of Islamic Accounting Standard No. (2) Murabaha and Murabaha to the purchase orderer In Islamic Kuwaiti Banks and the obstacles to their application - Saleh, Abdulmajid Obaid Hasan; S alazemi, Arsheed; Anter foaid al, Anter (AlHikmah Research and Publication Centre, 2019)
هدفت هذه الدراسة إلى التعرف على مدى تطبيق المعيار المحاسبي الإسلامي رقم (2) المرابحة والمرابحة بالشراء في البنوك الإسلامية الكويتية ومعوقات تطبيقها. واعتمد الباحث على عينه من مديري الإدارات العليا والإدارات الوسطى، والمديرين الماليين والمحاسبين العاملين في الدائرة المالية في البنوك الإسلامية الكويتية مكونة (91) مبحوثا، واعتمد الباحث على مصدرين رئيسين لجمع المعلومات والبيانات هما: البيانات الأولية والبيانات الثانوية، واستخدم عددا من أساليب الإحصاء الوصفي والاستدلالي. وتوصلت الدراسة إلى أن البنوك الإسلامية الكويتية تطبق المعيار المحاسبي الإسلامي رقم (2) عمليات المرابحة الداخلية. وتبين أن قسم الائتمان في البنك يقوم بحساب التكاليف التقديرية وبيان نسبة الأرباح المتوقعة من القيام بإجراء عملية المرابحة. وتبين أن هناك مجموعة من المعوقات تحول دون تطبيق المعيار المحاسبي الإسلامي رقم (2) المرابحة والمرابحة بالشراء في البنوك الإسلامية الكويتية. وفي ضوء ذلك قدمت الدراسة مجموعة من التوصيات أهمها: قيام قسم الائتمان في البنوك الإسلامية بتوفير التشريعات والإجراءات اللازمة لضمان شراء البضاعة بثمن المبيع مضافا إليه هامش ربح محدد حسب سياسة البنك. *************************************************************************** The study aims to identify the extent of application of Islamic accounting standard No. (2) murabaha and murabaha to the purchase orderer In Islamic Kuwaiti banks and the obstacles to their application. The researcher relied on two main sources to collect information and data: primary data and secondary data, and used a number of descriptive and explanatory statistics methods. The study concluded that the Islamic banks in Kuwait apply Islamic accounting standard No. (2) internal Murabaha transactions. It was found that the Bank's credit department calculates the estimated costs and the percentage of profits expected from conducting the Murabaha transaction. It was found that there are a number of obstacles that prevent the application of Islamic Accounting Standard No. (2) Murabaha and Murabaha in Kuwaiti Islamic Banks. In light of this, the study presented a number of recommendations, the most important of which is: The credit department of Islamic banks provides the necessary legislation and procedures to guarantee the purchase of the goods at the selling price plus a profit margin specified in accordance with the Bank's policy.